Charity eaudiobook - Watts, Beverley (Shackleford Sisters, 2024)
In this funny Regency romance series, the Shackleford sisters descend on a Regency society that doesn't know what's hit it... While Charity Shackleford might be considered far more outspoken than her twin sister Chastity, she was much less inclined to make a complete cake of herself. Something her twin appeared to be doing with increasing regularity. Indeed, when details of Chastity's latest faux pas threatened to travel beyond the confines of Blackmore, it appeared that removing her from the vicinity was the only answer. Naturally, as always, Grace, the eldest daughter and current Duchess of Blackmore was tasked with picking up the pieces. Unfortunately, just as she was about to inform their father of her intention to take Chastity for a short holiday to their sister Faith in Torquay, the Reverend was unexpectedly called upon to attend his curate's sadly dying mother. Firmly of the opinion that their father could not be trusted to stay out of mischief long enough to give anybody the last rites, Grace instructed Charity to accompany him. On reaching the trading port of Dartmouth, Charity quickly learned that nothing was as it seemed. Indeed, she discovered her sister's worst fears were well founded as she, her father and Percy found themself embroiled in a long-standing conspiracy involving smuggling and murder. Only the arrival of the mysterious Jago Carlyon stood between them and the infamous leader of the Hope Cove smuggling ring. Struggling to fight her undeniable attraction to the handsome Cornishman, Charity had to decide whether he could be trusted with her heart, or more importantly her life. Perfect for fans of Regency Romances with wit and humor and a little bit of steam...